Satisfaction Level of Inpatient Food Services for Patients at RSUD Meuraxa Hospital in Banda Aceh - Nurhafidza, Fadyassyifa; T. Alamsyah; Nur, Muhammad (PT Inovasi Pratama Internasional, 2024)
Hospitals are one of the crucial healthcare facilities that play a vital role in supporting healthcare efforts. Patient satisfaction or dissatisfaction is significantly influenced by the expected quality of services, particularly in hospitals. One of the success indicators in nutritional services is the satisfaction level of patients with the food they receive, as it positively contributes to the patients' healing process. These efforts also play a crucial role in supporting the recovery of patients. This research aims to assess the level of satisfaction with food services in terms of taste, presentation, and serving among inpatients at RSUD Meuraxa in Banda Aceh. The research method employed is descriptive quantitative research, aiming to provide an overview of patient satisfaction with food services at RSUD Meuraxa. Data were collected from 50 randomly selected respondents using an instrument that utilized a Likert scale with four options. The results of this study indicate that the majority of respondents are highly satisfied with the food services. A total of 90.0% of respondents stated that the food served at the hospital is delicious. Additionally, 70.0% of respondents found the food presentation to be appealing, and 96% of respondents considered the food serving to be excellent for inpatients at RSUD Meuraxa. Of all the satisfaction aspects measured, 86.0% of respondents expressed their satisfaction with the food services provided to inpatients at the hospital.